PERAN ORANG TUA DALAM MEMBENTUK SIKAP MANDIRI ANAK USIA DINI PADA MASA PANDEMI COVID-19 - Naeli Mutmainah; Hisam Ahyani; Ahmad Hapidin (Aulada : Jurnal Pendidikan dan Perkembangan Anak, 2021)
The formation of independence is a process of inculcating a personality for a better future better especially the generation that is in its golden age. Independence means as a character that can make early childhood able to stand alone, not dependent others, especially parents. Parents, especially mothers, have an important role in the process formation of children's independence. This type of research is analyzed using research methods qualitative descriptive with data collection techniques through observation and interviews. As for The purpose of this study is to find out how big the role of working mothers is in shaping independent attitude of early childhood, parenting and supporting and inhibiting factors. From the results of the study, it was found that the role of working mothers in forming children's independent attitudes, namely: as a motivator, role as supervisor, role as educator & mentor, role as a role model. As for the most appropriate parenting pattern applied by parents in form a child's independent attitude that is democratic parenting. While the factors that become supporters of the formation of independence, namely: the environment, a sense of love and affection, as well as patterns of foster. inhibiting factors, namely: the child's mood, inappropriate parenting, peers or playmates, time and opportunity.